1998
DOI: 10.1021/jo980201+
|View full text |Cite
|
Sign up to set email alerts
|

Tetrakis(dimethylamino)ethylene as a Useful Reductant of Some Bromodifluoromethyl Heterocycles. Application to the Synthesis of New gem-Difluorinated Heteroarylated Compounds

Abstract: The cyclic voltammetry of the reductive cleavage of some bromodifluoromethyl heterocycles and of the oxidation of the tetrakis(dimethylamino)ethylene was investigated in N,N-dimethylformamide and acetonitrile, at an inert electrode. The systematic investigation of the kinetics of the electrochemical reduction of this series of bromodifluoromethyl compounds provides clear evidence of a concerted electron-transfer−bond-breaking mechanism. Application of the theory of the dissociative electron transfer allowed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 47 publications
5
57
0
4
Order By: Relevance
“…Evidence of the 2-(difluoromethyl)benzoxazole radical as an intermediate in these reactions was demonstrated by the observation of the radical addition to 2,3-dihydrofuran, an electron-rich olefinic substrate (Scheme 10); TDAE should be added dropwise to a DMF solution of 1 and 2,3-dihydrofuran in order to detect the radical adduct 13 [11]. Unfortunately all the alcohol adducts obtained in this study were devoid of any anti-HIV-1 activity.…”
Section: Halogenodifluoromethylated Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence of the 2-(difluoromethyl)benzoxazole radical as an intermediate in these reactions was demonstrated by the observation of the radical addition to 2,3-dihydrofuran, an electron-rich olefinic substrate (Scheme 10); TDAE should be added dropwise to a DMF solution of 1 and 2,3-dihydrofuran in order to detect the radical adduct 13 [11]. Unfortunately all the alcohol adducts obtained in this study were devoid of any anti-HIV-1 activity.…”
Section: Halogenodifluoromethylated Substratesmentioning
confidence: 99%
“…The solution (which slowly became orange) was warmed up to room temperature and after 1 h at this temperature, was filtered (to remove the TDAE 2+ 2Br À ), hydrolyzed and workedup. The corresponding alcohol adduct 2 was obtained in a 65% isolated yield, and the methodology could be extended to a series of aromatic, heterocyclic aldehydes as well as ketones, giving access to new alcohol adducts 3-11 in moderate to good yields [4,11] (Scheme 8). In addition 5-(bromodifluoromethyl)-3-phenyl-1,2,4-oxadiazole 12 [9] was also found to be a good substrate in such TDAE-mediated carbon-carbon-coupling reactions [11].…”
Section: Halogenodifluoromethylated Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we decided to prepare such analogs by replacing one CH 2 by a CF 2 and the other CH 2 by different easily accessible functionalities, such as a CHOH and a heteroatom Y (Y = S, O). We have already presented the synthesis of the compounds having the -CF 2 CHOH spacer in a preceding paper [11] as well as a series of the -CF 2 YAr analogs [12]; these molecules were evaluated for biological activity, and it was found that some of the -CF 2 S derivatives had interesting activity, with the best being compound 3 (EC 50 = 64.6 nM) [12]. A comparison of the activity of the fluorine-containing compound 5, to the hydrogensubstituted analog 6, leads to the conclusion that fluorine substitution is responsible for a 10-fold increase in activity.…”
Section: Introductionmentioning
confidence: 99%
“…Tetrakis(dimethylamino)ethylene (TDAE) is a reducing agent which reacts with halogenated derivatives to generate an anion in soft conditions by means of two sequential transfers of one electron [134][135][136].We showed that from o-or p-nitrobenzyl chlorides, TDAE was able to generate a nitrobenzylic carbanion capable of reacting with various electrophiles [137].Since 2003 and by means of this strategy, we have developed several reactions between nitrobenzylic substrates, heterocyclic or quinonic and carbonylated electrophile series such as aldehydes [137][138][139][140], ketones [137][138][139][140], -ketoesters [141][142][143], -ketolactames [144], -diketones [145,146] and diethyl ketomalonate [141][142][143], leading to adducts of the corresponding alcohol. In line with our program on the study of electron transfer reactions of bioreducible alkylating agents and the preparation of new nitroimidazoles with biological potential, we synthesized new highly functionalized 5-nitro-1H-imidazoles from 4-[4-(chloromethyl)phenyl]-1,2-dimethyl-5-nitro-1H-imidazole 83 and various carbonylated aromatic derivatives or -carbonylated-ester by using the TDAE methodology.…”
Section: Ivb Tetrakis(dimethylamino)ethylene (Tdae) Methodology In mentioning
confidence: 99%